2005
DOI: 10.1248/cpb.53.1439
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Anion-Scavenging Effect of 2-Amino-1,3-selenazoles

Abstract: We investigated the superoxide anion scavenging effects of thirteen 2-amino-1,3-selenazoles using a highly sensitive quantitative chemiluminescence method. At 166 m mM, the 2-amino-1,3-selenazoles scavenged in the range of 14.3 to 96.7% of O 2 ؊ . 2-Piperidino-1,3-selenazole and 4-phenyl-2-piperidino-1,3-selenazole exhibited the strongest superoxide anion-scavenging activity among the 2-amino-1,3-selenazoles. The 50% inhibitory concentrations (IC 50 ) of 2-piperidino-1,3-selenazole and 4-phenyl-2-piperidino-1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Thus, the 1 H NMR spectrum of 8a showed a signal at δ 4.93 ppm equivalent to the NH 2 group (D 2 O exchangeable), a singlet at δ 6.62 ppm indica-ting the coumarin H-4 and a multiplet at δ 7.26-7.40 ppm for the C 6 H 4 group. In addition, the 13 C NMR spectrum signals were consistent with the assigned structure. The reaction of either compound 8a or 8b with phenylisothiocyanate (9) gave the 7-phenylthiazolo [4',5':4,5] thieno [2,3-d]pyrimidine-6(7H)-thione derivatives 10a and 10b, respectively.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Thus, the 1 H NMR spectrum of 8a showed a signal at δ 4.93 ppm equivalent to the NH 2 group (D 2 O exchangeable), a singlet at δ 6.62 ppm indica-ting the coumarin H-4 and a multiplet at δ 7.26-7.40 ppm for the C 6 H 4 group. In addition, the 13 C NMR spectrum signals were consistent with the assigned structure. The reaction of either compound 8a or 8b with phenylisothiocyanate (9) gave the 7-phenylthiazolo [4',5':4,5] thieno [2,3-d]pyrimidine-6(7H)-thione derivatives 10a and 10b, respectively.…”
Section: Resultssupporting
confidence: 68%
“…Thus, the 1 H NMR spectrum showed a singlet at δ 4.28 ppm equivalent to the thiazole CH 2 group, a singlet at δ 6.52 ppm indicating the coumarin 4H, a multiplet at δ 7.28-7.38 ppm for the C 6 H 4 group. Moreover, the 13 C NMR spectrum shoSheme 1. Synthesis of compounds 3, 6a-c and 7a-c wed beside the expected signals, δ 58.6 ppm indicating the presence of the thiazole CH 2 , two signals at δ 164.3, 168.6 ppm equivalent to the two CO groups and a signal at δ 170.3 ppm for the C=N.…”
Section: Resultsmentioning
confidence: 97%
“…Previously, we systematically synthesized various organic selenium compounds, including selenocarbamates, selenoureas, thioureas, tertiary selenoamide compounds, 2-amino-1,3-selenazoles, and bis-(2-amino-5-selenazoyl) ketones, and demonstrated their SOSA by using the same chemiluminescence method. The IC 50 values of these compounds ranged from approximately 0.1 to 100 µM (Takahashi et al, 2004;Sekiguchi et al, 2005;Takahashi et al, 2005a;Takahashi et al, 2005b;Sekiguchi et al, 2006). The SOSA of compound b might be relatively low compared with that of other compounds such as selenocarbamates, selenoureas, thioureas, tertiary selenoamide, and ebselen.…”
Section: Discussionmentioning
confidence: 97%
“…4 Recently, it was reported that 2-piperidino-and 4-phenyl-2-piperidino-1,3-selenazoles exhibit strong superoxide anion-scavening activity 5 , while 2-piperidino-and 2-morpholino-5-chloroacetyl-1, 3-selenazoles (4a, b) show antioxidant activity and strongly inhibit lipopolysaccharide-induced nitric oxide release from microglial cells. 6 Moreover, 2-amino-1,3-selenazole derivatives found application in the synthesis of organic dyes.…”
Section: Introductionmentioning
confidence: 99%